DECENTRALIZATION AND DEMOCRACY: EVALUATING THE PERFORMANCE OF REGIONAL AUTONOMY IN IMPROVING PUBLIC WELFARE - Bao, Bonefasius; Suardi, Soni (PT. Hafasy Dwi Nawasena, 2025)
This study evaluates the relationship between decentralization, local democracy, and public welfare improvement in Indonesia through a systematic literature review of 38 academic studies published between 2015 and 2024. The findings indicate that regional autonomy has expanded democratic spaces and stimulated public service innovation, particularly in regions with strong fiscal capacity and progressive leadership. However, regional performance disparities remain evident, characterized by fiscal inequality, bureaucratic weaknesses, and patronage politics that hinder equitable welfare outcomes. This study highlights the need to strengthen local government capacity, enhance budget transparency, and promote meaningful public participation. It offers conceptual contributions by integrating governance and regional economic dimensions, and provides policy recommendations to ensure decentralization functions as an effective instrument for public welfare improvement.